Psychobiology of Attachment and Trauma—Some General Remarks From a Clinical Perspective - Lahousen, Theresa; Unterrainer, Human Friedrich; Kapfhammer, Hans-Peter (Frontiers in Psychiatry, 2019)
Attachment refers to a psychobiological principle that is deeply rooted in evolutionary development; it is thought to contribute a major advantage in the survival of the social group. Within individual development it indicates a primary motivational system that guides the initial transactions between mother and baby and furthermore mediates affective attunement and regulation. Psychosocial learning, in close interaction with genetics and epigenetics, also develops a decisive foundation for further brain development of the infant. Finally, the attachment pattern established forms an enduring, relational context for later affective, cognitive and social development of the child. As an unconsciously active matrix for future personal relationships it has a particular impact on the comprehensive psychological functions of empathy and mentalization. Early adverse and traumatic experiences or major emotional neglect may lead to different levels of security versus insecurity or disorientation-disorganization of the attachment pattern that corresponds to characteristic features of neurobiological regulation.